The multimodal concept of hemodynamic stabilization - Krisztián eTánczos; Márton eNémeth; Zsolt eMolnár (Frontiers Media S.A., 2014)
Hemodynamic instability often leads to hypoperfusion, which has a significant impact on outcome in both medical and surgical patients. Measures to detect and treat tissue hypoperfusion early by correcting the imbalance between oxygen delivery and consumption is of particular importance. There are several studies targeting different hemodynamic end-points in order to investigate the effects of goal-directed therapy on outcome. A so called multimodal concept putting several variables in context follows simple logic and may provide a broader picture. Furthermore, rather than treating population based normal values of certain indices, this concept can be translated into the individualized patient care to reach adequate oxygen supply and tissue oxygenation in order to avoid under-, or over-resuscitation, which are equally harmful. The purpose of this review is to give an overview of current data providing the basis of this a multimodal, individualized approach of hemodynamic monitoring and treatment.